Successful Transfer of a Model T-DNA Plasmid to E. coli Revealed Its Dependence on Recipient RecA and the Preference of VirD2 Relaxase for Eukaryotes Rather Than Bacteria as Recipients - Ohmine, Yuta; Kiyokawa, Kazuya; Yunoki, Kazuya; Yamamoto, Shinji; Moriguchi, Kazuki; Suzuki, Katsunori (Frontiers in Microbiology, 2018)
In Agrobacterium–mediated transformation (AMT) of plants, single-strand (ss) T-DNA covalently linked with VirD2 protein moves through a bacterial type IV secretion channel called VirB/D4. This transport system originates from conjugal plasmid transfer systems of bacteria. Relaxase VirD2 and equivalent protein Mob play essential roles in T-DNA transfer and mobilizable plasmid transfer, respectively. This study challenged transfer of a model T-DNA plasmid that contains no left border but a right border sequence as an origin of transfer, and transfer of a mobilizable plasmid through the VirB/D4 apparatus to Escherichia coli, Agrobacterium and yeast to compare VirD2-driven and Mob-driven transfers. AMT was successfully achieved by both type transfers to the three recipient organisms. VirD2-driven AMT of the two bacteria was less efficient than Mob-driven one. In contrast, AMT of yeast guided by VirD2 was more efficient than that by Mob. Analysis of plasmid DNAs recovered from the VirD2-driven AMT colonies showed the original plasmid structure. These data indicate that VirD2 retains basically most of its important function necessary in recipient bacterial cells, but has largely adapted to eukaryotes rather than bacteria. The high AMT efficiency of yeast suggests that VirD2 can bring ssDNA abundantly also to recipient bacterial cells but is inferior to Mob in some process leading to the formation of double-stranded circular DNA in bacteria. This study also revealed involvement of recipient recA gene greatly in the VirD2-dependent AMT, and only partially in Mob-dependent AMT. The apparent difference of the recA gene requirement between the two type AMTs suggests that VirD2 is worse at re-circularization leading to completion of complementary DNA synthesis than Mob in bacteria.